103.5=x+((x*0.03)+0.5)

Simple and best practice solution for 103.5=x+((x*0.03)+0.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 103.5=x+((x*0.03)+0.5) equation:


Simplifying
103.5 = x + ((x * 0.03) + 0.5)

Reorder the terms for easier multiplication:
103.5 = x + ((0.03x) + 0.5)

Reorder the terms:
103.5 = x + (0.5 + (0.03x))

Remove parenthesis around (0.5 + (0.03x))
103.5 = x + 0.5 + (0.03x)

Reorder the terms:
103.5 = 0.5 + x + (0.03x)

Combine like terms: x + (0.03x) = 1.03x
103.5 = 0.5 + 1.03x

Solving
103.5 = 0.5 + 1.03x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.03x' to each side of the equation.
103.5 + -1.03x = 0.5 + 1.03x + -1.03x

Combine like terms: 1.03x + -1.03x = 0.00
103.5 + -1.03x = 0.5 + 0.00
103.5 + -1.03x = 0.5

Add '-103.5' to each side of the equation.
103.5 + -103.5 + -1.03x = 0.5 + -103.5

Combine like terms: 103.5 + -103.5 = 0.0
0.0 + -1.03x = 0.5 + -103.5
-1.03x = 0.5 + -103.5

Combine like terms: 0.5 + -103.5 = -103
-1.03x = -103

Divide each side by '-1.03'.
x = 100

Simplifying
x = 100

See similar equations:

| 4n+5=7n+11 | | f=6x-1+3x | | (-16)(1/2)^-4 | | z-4/21 | | 2d+.16=6(.33d+1) | | 4.25z=55.25 | | 1km=42mi | | 25=15m | | .25(n-6)=.25n-1.33 | | 7-5-5x=9 | | 4(3x-5)+7(7x-8)-3x-6= | | 34+x=44+3x | | x^2+(-1-i)*x+5i=0 | | 4x9=30-k/6 | | 3.6t=5.4+3.3y | | 4/3×3.14×18^2 | | 8x+5.5=63 | | 2-3x-5x^2=0 | | (x-3)/5=1-(a/3) | | 2(X+3)+2(3x-2)=58 | | 7/12x=28/3 | | X(x+3)=x(x+6)-15 | | 1.4+(2.3)= | | Xsquare+3x-4=0 | | 3500+1680x=220650 | | P-19=17 | | 12=-6k+4+2 | | 3a^2+30a+100=0 | | -8=-3k-5k | | log(8x+2)=6 | | -18=5x+4x | | 7(11+1)+5(11+1)=14 |

Equations solver categories